2011
DOI: 10.1007/s11104-011-0966-9
|View full text |Cite
|
Sign up to set email alerts
|

Composition of photosynthetic organisms and diurnal changes of photosynthetic efficiency in algae and moss crusts

Abstract: AbstractsAims In Dalateqi region of Inner Mongolia (at eastern edge of Qubqi Desert), man-made algae crusts were constructed with two filamentous cyanobacteria. Two to three years later, the algae crusts began to succeed to moss crusts under some microterrain conditions. In order to characterize the community structure and compare the photosynthetic characteristics in different successional stages of biological soil crusts (BSCs). Methods This paper studied composition of photosynthetic organisms and diurnal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 58 publications
5
61
0
3
Order By: Relevance
“…Crust organisms also promoted the conversion of sand into soil by increasing soil nutrients and improving topsoil texture. 6,18 In addition, the increased dust deposition on crust surface also could increase soil organic matters and nutrients. 27 Succession of Vascular Vegetation Communities.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crust organisms also promoted the conversion of sand into soil by increasing soil nutrients and improving topsoil texture. 6,18 In addition, the increased dust deposition on crust surface also could increase soil organic matters and nutrients. 27 Succession of Vascular Vegetation Communities.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In our experimental region, with cyanobacterial inoculation, cyanobacterial crusts formed quickly and in some micoenvironments gradually succeeded to moss crusts 2−3 years later. 17,18 In the survey of Wang et al, 19 it was found the diverse vegetation communities (17 species of vascular plants in total) were established on the different sides of dunes after 3 years of cyanobacterial inoculation. However, the mechanisms of formation, development, succession of BSCs, revegetation of vascular plants, and succession of vegetation communities after cyanobacterial inoculation are still unknown.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In Dalate Banner region, after inoculating the two filamentous cyanobacteria, cyanobacterial crusts formed quickly and gradually succeed to moss crusts on the shady side of dunes 2-3 years later (Lan et al, 2012b). With the development and succession from cyanobacterial crusts to moss crusts, moss coverage gradually increased, photosynthetic biomass and microbial CFU also increased significantly (P b 0.05), while cyanobacterial and algal biomass decreased (P b 0.05; Fig.…”
Section: Biomass Change With Crust Development and Successionmentioning
confidence: 92%
“…Based on our previous observations, in Shapotou region (at the southeast edge of Tengger Desert) BSCs generally succeed from cyanobacterial crusts to lichen and moss crusts along a pathway of "cyanobacterial crusts, cyanobacteriallichen crusts, lichen crusts, lichen-moss crusts and moss crusts" (Lan et al, 2012a(Lan et al, , 2013. However in Dalate Banner region (mainly in Jiefangtan; at the eastern edge of Qubqi Desert), BSCs directly succeed from cyanobacterial crusts to moss crusts (Lan et al, 2012b(Lan et al, , 2014. As a whole, three different successional stages including cyanobacterial, lichen and moss crusts are found in Shapotou region, while only cyanobacterial and moss crusts appear in Dalate Banner region.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation